Local products, and regional and traditional dishes, in the hotel food and beverage industry as examples of innovations used by five-star hotels in Poland - Poreda, Anna (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
The catering industry is one of the most rapidly growing branches of the economy. However, it is worth noting that despite the introduction of many innovations and following current trends, the catering industry has not parted with tradition. Tradition is understood as the use of regional products, the use of national cuisine or the serving of regional dishes. Hotel catering is required to be highly versatile. It is also supposed to meet the nutritional needs of various hotel guests. Despite restaurants focusing on one type of cuisine, there is a persistent tendency to serve breakfasts that suit the needs of the largest group of guests, regardless of their country of origin or eating habits. Breakfasts are the most popular catering service in hotels. More and more hoteliers are deciding to extend this offer with products and dishes of their own devising, or of local or traditional-regional origin. This choice has a positive influence on the competitive advantage among the establishments, and at the same time has a positive impact on the development of the local market. Hoteliers are eager to boast of using such products on their menus, additionally contributing to the education of guests about the cuisine of the country or region. In this article, the author presents examples of using traditional dishes in hotel restaurants. With particular emphasis on such practices in five-star hotels in Poland.